Using on-line analyzers and RAC parameters to determine the amount of TN and TP pollutants discharged from Poland into the Baltic Sea - Wilk, Paweł; Grabarczyk, Adam (Geology, Geophysics and Environment, 2018)
Despite the numerous measures taken to protect its environment for many years, Poland is among the top countries with the largest contributing share in the pollution of the Baltic Sea. It is undoubtedly the case that we are dealing with excesses in the permissible concentrations of total nitrogen (TN) and total phosphorus (TP) on many sections of Polish rivers. However, in order to be able to thoroughly analyze this problem, it is first necessary to increase the frequency of TN and TP monitoring in surface waters. The article presents the first results obtained from the TN and TP monitoring system launched in 2016 at the IMGW-PIB on the calculation profile Szczecin (the Odra River) and Tczew (the Vistula River). The on-line analyzers installed for this purpose make it possible to perform measurements several times a day, allowing for the assessment of diurnal and seasonal variations of TN and TP. Using the results obtained, the daily values of the River Absorption Capacity (RAC) parameter were also calculated. The obtained results showed that, in general, the value of the RAC parameter on the analyzed calculation profiles was positive for both TN and TP throughout the entire period, irrespective of the time of year.